2000
DOI: 10.1002/1531-8249(200002)47:2<229::aid-ana13>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Profile of endothelial and leukocyte activation in fabry patients

Abstract: Fabry disease is an X‐linked recessive disorder resulting in the deposition of globotriaosylceramide in numerous cell types including vascular endothelial cells. Because this disease is associated with vascular injury and a high recurrence rate of thrombotic events, measurements of factors regulating endothelium and leukocyte interaction may provide insight into the mechanisms leading to a prothrombotic state. Twenty‐five patients with Fabry disease and 25 control subjects participated in the study. Plasma fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(99 citation statements)
references
References 29 publications
8
86
0
5
Order By: Relevance
“…Lyso-GL-3 concentration was significantly reduced from baseline at each successive Clinical assessment, and individual patient values of plasma lyso-GL-3 concentration fluctuated less than did those of plasma and urine GL-3 concentrations (data not shown). Although during the past decade attention has largely focused on the pathogenic role of GL-3 in FD (DeGraba et al 2000;Park et al 2011;Shen et al 2008), the importance of lyso-GL-3 in the FD process has become evident. For example, exposure of smooth muscle cells in vitro to lyso-GL-3 at concentrations similar to those seen in patients with FD (e.g., in the patients treated for 12 months with agalsidase alfa or beta at 0.2 mg/kg [van Breemen et al 2011]) stimulates proliferation of the smooth muscle cells (Aerts et al 2008), a finding consistent with the increased intima-media thickness observed in patients with FD (Barbey et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Lyso-GL-3 concentration was significantly reduced from baseline at each successive Clinical assessment, and individual patient values of plasma lyso-GL-3 concentration fluctuated less than did those of plasma and urine GL-3 concentrations (data not shown). Although during the past decade attention has largely focused on the pathogenic role of GL-3 in FD (DeGraba et al 2000;Park et al 2011;Shen et al 2008), the importance of lyso-GL-3 in the FD process has become evident. For example, exposure of smooth muscle cells in vitro to lyso-GL-3 at concentrations similar to those seen in patients with FD (e.g., in the patients treated for 12 months with agalsidase alfa or beta at 0.2 mg/kg [van Breemen et al 2011]) stimulates proliferation of the smooth muscle cells (Aerts et al 2008), a finding consistent with the increased intima-media thickness observed in patients with FD (Barbey et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…More systemic biomarkers, including vascular ones, indicated that inflammation or growth factors should be evaluated (40,41).…”
Section: Other Biomarkersmentioning
confidence: 99%
“…Dr. Schiffmann's group has focused its studies on vascular disorder of Fabry disease, and has demonstrated the presence of abnormalities in blood flow, vessel wall, and blood components (56). In terms of alterations of blood components, they have detected an inflammation-activated state in endothelium and leukocytes in Fabry disease (57,58).…”
Section: Pathophysiologymentioning
confidence: 99%
“…The gene NAIP (Neuronal apoptosis inhibitory protein) associated with inflammation was found to be upregulated in Fabry children (63). Exposure of endothelial cells to Gb3 resulted in increased intracellular production of reactive oxygen species (57).…”
Section: Pathophysiologymentioning
confidence: 99%